2018
DOI: 10.1182/blood-2017-09-808816
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL mediates and sustains constitutive NF-κB activation in LGL leukemia

Abstract: Large granular lymphocyte (LGL) leukemia results from clonal expansion of CD3 cytotoxic T lymphocytes or CD3 natural killer (NK) cells. Chronic antigen stimulation is postulated to promote long-term survival of LGL leukemia cells through constitutive activation of multiple survival pathways, resulting in global dysregulation of apoptosis and resistance to activation-induced cell death. We reported previously that nuclear factor κB (NF-κB) is a central regulator of the survival network for leukemic LGL. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…From the overlapping cytokines, we found some potential biomarkers to pursue. Several studies found IL-6 and/or TRAIL were elevated in TLGLL serum/plasma samples [40, 50, 51, 54], which we also observed in the NK-LGLL patients in this study. Interestingly, all three T-LGLL studies showed IL-8 was significantly elevated in T-LGLL compared to normal donors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…From the overlapping cytokines, we found some potential biomarkers to pursue. Several studies found IL-6 and/or TRAIL were elevated in TLGLL serum/plasma samples [40, 50, 51, 54], which we also observed in the NK-LGLL patients in this study. Interestingly, all three T-LGLL studies showed IL-8 was significantly elevated in T-LGLL compared to normal donors.…”
Section: Discussionsupporting
confidence: 87%
“…G-CSF/CSF-3 and GM-CSF are colony stimulating factors that typically target stem cells in the bone marrow for the purpose of granulocyte production [11]. TRAIL, which our lab has found to be elevated in LGLL [51], is a tumor necrosis family ligand that typically induces apoptosis through a death receptor [52]. Epidermal growth factor (EGF) can signal through STAT5 in trophoblastic cell lines [53], but its potential role in leukemia is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic inhibition is also mediated by increased activation of the PI3K/Akt signaling pathway via RANTES, IL-18, and MIP-1b at higher serum concentrations in LGL patients compared with healthy subjects [ 101 , 102 ]. Moreover, hyperactivation of NF-κB through TRAIL receptor activation can also lead to increased resistance to apoptosis in LGLs [ 103 ]. In addition, circulating levels of IFN-α2, IFN-γ, monocyte chemoattractant protein-1, epidermal growth factor, IL-6, IL-8, IL-10, IL-1β, IL-12p35, IL-1Ra, and MIP1-a are increased in the sera of LGL leukemia patients ( Table 3 ) [ 104 , 105 ].…”
Section: Large Granular Lymphocyte Leukemiamentioning
confidence: 99%
“…RNA-based assays enable analysis of basal expression profiles and responses to antigen or mitogen stimulation (3,4). Human PBMCs are a common source of RNA as collection of blood is less invasive and allows in-depth monitoring of many aspects of immunobiology (1,5) including identification, classification and prognosis of cancers (6)(7)(8)(9)(10)(11) monitoring inflammation (12,13), and evaluating therapeutic efficacy (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%